TRANSLATION PROJECT MANAGEMENT (Ustozlar uchun, 2026)
This article analyzes the theoretical foundations of translation project management, the lifecycle stages, the system of resources and roles, quality assurance mechanisms, and potential risks. The research is based on project management standards scholarly sources in translation studies, and practical project experience. The article outlines management requirements for different types of translation projects, proposes quality assessment criteria, and suggests risk management strategies. The empirical section evaluates the effectiveness of the proposed methodology using various types of projects as examples. The conclusion identifies success factors in translation project management and future development directions.